2012
DOI: 10.1002/asia.201200730
|View full text |Cite
|
Sign up to set email alerts
|

Heterocycle‐linked Phenylbenzyl Amides as Novel TRPV1 Antagonists and Their TRPV1 Binding Modes: Constraint‐Induced Enhancement of In Vitro and In Vivo Activities

Abstract: A series of heterocycle-linked constrained phenylbenzyl amides were found to be TRPV1 antagonists with promising in vivo profiles. In particular, one of the analogues containing a furan linker exhibited excellent TRPV1 antagonistic activity and in vivo analgesic efficacy. In addition, the binding modes of dibenzyl thiourea, benzylphenethyl amide, and furan-linked phenylbenzyl amide were examined by using the flexible docking study within the rTRPV1 homology model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…in their models before the determination of the cryomicroscopy TRPV1 structure. In those models authors reported HBs between the 4-(methylsulfonylamino)benzyl group and G558 34 , 42 , I564 41 or K571 21 ; however, these residues are not placed at the TRPV1’s binding site in the cryomicroscopy TRPV1 structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in their models before the determination of the cryomicroscopy TRPV1 structure. In those models authors reported HBs between the 4-(methylsulfonylamino)benzyl group and G558 34 , 42 , I564 41 or K571 21 ; however, these residues are not placed at the TRPV1’s binding site in the cryomicroscopy TRPV1 structure.…”
Section: Resultsmentioning
confidence: 99%
“…Then, they performed flexible docking analysis using this model and they found a good agreement with their mutation data. Over the next years, the same group used this model to propose the docked poses of different sulfonylaminobenzyl derivatives 21 , 34 , 41 , 42 . This model used properly the structural information what was known at the time and provided clarification on various issues related to the interactions between TRPV1 and capsaicin-like ligands; however, it had some shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerization of methyl methacrylate in water solution was conducted by the polymerization of γ-MPS at the surface of NSB-γ-MPS with MMA to form NSB-PMMA 14 . Copolymerization of the γ-MPS on nano silica ball with acrylonitrile, styrene and methyl methacrylate monomer was performed at water solvent environment to form NSB-MAS 15 .…”
Section: Methodsmentioning
confidence: 99%
“…We have previously developed TRPV1 antagonists with various scaffolds and successfully discovered SC0030 (or JYL1421, 5 , Figure ), which showed 60 fold higher potency than capsazepine . Based on the previous studies and our reported work, we planned to explore the effect of SC0030 on osteoclastogenesis involved in bone resorption process of osteoporosis.…”
Section: Acknowledgmentsmentioning
confidence: 99%